Incentive Contracts in Delegated Portfolio Management - Li, C. Wei; Tiwari, Ashish (Review of Financial Studies, 2009)
This article analyzes optimal nonlinear portfolio management contracts. We consider a setting in which the investor faces moral hazard with respect to the effort and risk choices of the portfolio manager. The employment contract promises the manager: (i) a fixed payment, (ii) a proportional asset-based fee, (iii) a benchmark-linked fulcrum fee, and (iv) a benchmark-linked option-type “bonus” incentive fee. We show that the option-type incentive helps overcome the effort-underinvestment problem that undermines linear contracts. More generally, we find that for the set of contracts we consider, with the appropriate choice of benchmark it is always optimal to include a bonus incentive fee in the contract. We derive the conditions that such a benchmark must satisfy. Our results suggest that current regulatory restrictions on asymmetric performance-based fees in mutual fund advisory contracts may be costly.